2019
DOI: 10.1186/s12891-019-2797-4
|View full text |Cite
|
Sign up to set email alerts
|

Ten-year results of concentrated autologous bone marrow aspirate transplantation for osteonecrosis of the femoral head: a retrospective study

Abstract: Background Idiopathic osteonecrosis of the femoral head (ONFH) occurs at a relatively younger age. It is therefore important to prevent the resultant femoral head collapse and requirement of total hip arthroplasty in these patients. In 2003, we initiated concentrated autologous bone marrow aspirate transplantation (CABMAT), a joint-preserving treatment for ONFH, at our institution. Here, we report the long-term results of CABMAT treatment. Methods We retrospectively col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
1
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 33 publications
1
22
1
1
Order By: Relevance
“…In contrast, in Japan, CD has not been performed at all except for biopsy purposes. Recently, CD‐based cell therapy has become available at just one university hospital in Japan 21 .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in Japan, CD has not been performed at all except for biopsy purposes. Recently, CD‐based cell therapy has become available at just one university hospital in Japan 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported low efficacy of cell therapy in advanced ONFH patients (Table 3 ). Tomaru et al [ 23 ] reported a 43.2% (16/37) survival rate at 12 years postoperatively using bone marrow mononuclear cell (BMMNC) transplantation for advanced ONFH [ 23 ]. Wang et al also reported a 66.6% (6/9) survival rate with BMMNC therapy at 2.3 years postoperatively [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“… 13 , 14 The THA conversion rate certainly remains low with AALCO treatment compared to 75% THA conversion rate reported in patients with natural progression to osteoarthritis resulting from osteonecrosis of the femoral head. 15 , 16 A randomized study found autologous osteoblastic cells implantation to be more efficacious than bone marrow implantation as an adjunct to core decompression. The disease progression rate was found to be 20% in patients who had undergone autologous osteoblasts implantation vs 47% in patients in the bone marrow implantation group.…”
Section: Discussionmentioning
confidence: 99%